العلاقة بين الهطل المطري والجريان النهري في حوض السفرقية - الأسعد, علي; علي, ربا (Latakia University Journal -Engineering Sciences Series, 2018)
يقع الحوض الساكب (السفرقية) على السفوح الغربية لسلسلة الجبال الساحلية، وتبلغ مساحته km2 132.58، وهو يشكّل جزءاً من الحوض الساكب لنهر الروس، ويبدأ مجرى النهر على ارتفاع 1200م، وتلتقي مجموعة روافد فتشكّل نهر الروس الذي يصبّ في البحر المتوسط. وشُيّد سد صلاح الدين لتخزين 10 MCM على مجرى النهر عند موقع تلاقي نهر القرداحة مع نهر الشحادة. تهدف الدراسة إلى تحديد العلاقة بين الهطل المطري والجريان السطحي في حوض السفرقية. واعتمد البحث على التحليل الإحصائي لبيانات الهطل المطري والجريان، وبيّنت الدراسة أنَّ الكمية الوسطية للهطل المطري السنوي تبلغ MCM 159.6، والكميّة الوسطية للجريان السطحي تبلغ 9.4 MCM خلال فترة الدراسة (2012-2010 )، ومن ثَمّ فإنّ قيمة عامل الجريان السطحي تبلغ 0.06؛ أي أنّ الفواقد المائية كبيرة جداً، وتمّ استنتاج علاقة رياضية تسمح بتقدير كميات الجريان السطحي اعتماداً على قيم الهطل، لما لذلك من أهمية في دراسة المشروعات المائية لتخزين المياه وإدارتها، ودرء الفيضانات. The Alsafarqieh watershed is located on the western slopes of the coastal mountain range, Its area is 132.58 km2, It forms a part of the Alros river basin, The river starts at a height of 1200 m, A group of tributaries meet and form the Alros River, which flows into the Mediterranean Sea. Salaheddin Dam was constructed to store 10 MCM on the riverbed at the intersection of the Qurdaha River with the Shehada River. The study aims to determine the rainfall- runoff relationship in The Alsafarqieh watershed. The solution depends on the statistical analysis of precipitation and runoff data. Then the study found the mean annual precipitation is 159.6 MCM/year, and the mean annual flow into the Salaheddin lake was 9.4 MCM during the study period (2010-2012), so the runoff coefficient is 0.06. This indicates a significant water loss. A mathematical equation to predict the runoff quantities depending on the values ​​of precipitation, has been concluded. This is important to study water projects for water storage and flood prevention.